2009
DOI: 10.1159/000206852
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ Stratification and Correlation of Brain Magnetic Resonance Imaging Parameters with Disability Progression in Multiple Sclerosis

Abstract: Aims: The objective was to correlate the change in the lesion load (LL) and brain atrophy in patients with multiple sclerosis (MS) with progression of clinical disability, represented by the Expanded Disability Status Scale (EDSS), and to test if stratification of patients according to magnetic resonance imaging (MRI) criteria can increase the predictive ability of MRI for MS clinical development. Methods: 181 patients with clinically definite relapsing-remitting MS underwent MRI for a period of up to 5 years.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“…Considering the fact that excessive iron accumulation in the basal ganglia represents a neurodegenerative component of MS disease [7,33] and the observed strong correlations with gray matter atrophy, this study supports our hypothesis of patient stratification in those with mostly inflammatory components and in those with mostly degenerative components [34]; if we are not able to explain the identical disability status (disease manifestation) by corresponding MRI T 2 (or FLAIR) plaques, we could explain it as neurodegenerative changes (T 2 shortening, BPF). Our results are further evidence of the multifactorial etiology of MS and also that neurodegenerative changes play an important role in the etiology of disease.…”
Section: Discussionsupporting
confidence: 82%
“…Considering the fact that excessive iron accumulation in the basal ganglia represents a neurodegenerative component of MS disease [7,33] and the observed strong correlations with gray matter atrophy, this study supports our hypothesis of patient stratification in those with mostly inflammatory components and in those with mostly degenerative components [34]; if we are not able to explain the identical disability status (disease manifestation) by corresponding MRI T 2 (or FLAIR) plaques, we could explain it as neurodegenerative changes (T 2 shortening, BPF). Our results are further evidence of the multifactorial etiology of MS and also that neurodegenerative changes play an important role in the etiology of disease.…”
Section: Discussionsupporting
confidence: 82%
“…The two remaining longitudinal studies evaluated the predictive value of baseline brain volume and T2 lesion load for subsequent disability. In a 5-year study in patients with RRMS, Vaneckova et al demonstrated a significant correlation between increased brain atrophy in the first 2 years and EDSS score increase at years 4 and 5 in patients with a low lesion load at baseline ( p < 0.01); this correlation was not observed for those with a high baseline lesion burden ( 65 ). In another study, the probability of sustained disability progression (an EDSS score ≥3 within 3 years) was almost five times higher in patients with a low brain volume and a high T2 lesion volume compared with patients with a high brain volume and low T2 lesion volume ( 71 ).…”
Section: Resultsmentioning
confidence: 98%
“…Our own automated software (ScanViewCZ, designed by J.K.) was used to quantify T 2 LV in the FLAIR sequences and T 1 LV, brain atrophy and BPF in the T 1 -weighted 3D sequences [for detailed protocols, see [9], [10]]. Corpus callosum was measured on T 1 -weighted 3D images, using reconstructions of the sagittal slices.…”
Section: Methodsmentioning
confidence: 99%